Mobile Selves : Race, Migration, and Belonging in Peru and the U.S. - Berg, Ulla D. (Book collections on Project MUSE., 2015)
Mobile Selves illuminates how transnational communicative practices and forms of exchange produce new forms of kinship and social relations, as well as new forms of self-presentation and belonging for global labor migrants. It shows how migrants create new portrayals of themselves which work both to overcome the class and racial biases that they had faced in their home country, as well as to control the images they share of themselves with others back home. Migrant videos, for example, which document migrants' lives for family back home, are often sanitized to avoid causing worry. In this enga.